2006
DOI: 10.1007/s10641-006-9174-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating asymmetry in farmed Atlantic salmon (Salmo salar) juveniles: also a maternal matter?

Abstract: Developmental stability reflects the degree to which phenotypic expression is unaffected by random accidents or developmental noise. Developmental stability may be measured by phenodeviance or fluctuating asymmetry (FA), and estimation of developmental stability has attracted substantial interest because it appears to represent a relatively simple method to identify sub lethal stress exposure and to assess animal welfare. As a part of a long-term study, the work presented here primarily aimed to investigate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 59 publications
1
29
0
1
Order By: Relevance
“…In line with this, previous studies reported that exposing fish females to various stressors can be deleterious to offspring survival (Campbell et al, 1992;Eriksen et al, 2008;Mingist et al, 2007). In contrast, several experiments demonstrate no effect of parental stress on survival rates of the progeny (Small, 2004;Tierney et al, 2009;Eriksen et al, 2015).…”
Section: Discussionsupporting
confidence: 65%
“…In line with this, previous studies reported that exposing fish females to various stressors can be deleterious to offspring survival (Campbell et al, 1992;Eriksen et al, 2008;Mingist et al, 2007). In contrast, several experiments demonstrate no effect of parental stress on survival rates of the progeny (Small, 2004;Tierney et al, 2009;Eriksen et al, 2015).…”
Section: Discussionsupporting
confidence: 65%
“…Cortisol of maternal origin is present in the oocytes and embryos of several fish species (reviewed by Leatherland et al (2010)), and maternal plasma cortisol levels during the period of oocyte vitellogenesis determine oocyte cortisol content (Eriksen et al 2006, 2007, Veillette et al 2007. In salmonid fish, increased oocyte cortisol content brings about changes in the embryonic epigenome, resulting in changes in the phenotype of the progeny , 2011, Eriksen et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its potency as a regulator of intermediary metabolism in fish (Leatherland 2010, cortisol is involved in several aspects of normal gametogenesis and embryogenesis in fish. These include oocyte maturation and hydration (Milla et al 2006, hatching (Barry et al 1995, Sampath-Kumar et al 1995, sex differentiation (Hayashi et al 2010, embryo growth (Eriksen et al 2006, 2007, and modulation of the embryonic immune response . Thus, elevated cortisol levels in the oocytes, and therefore in early embryonic cells, have the potential to interfere profoundly with many aspects of normal embryogenesis (reviewed by Leatherland et al (2010Leatherland et al ( , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, previous studies on the effects of maternal glucocorticoids have used birds and fish as a model system [22][23][24][25], which are oviparous animals. In contrast, here we studied maternal stress in a mammal.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, such studies are scarce, and those that have been conducted mostly induce stress through a cortisol treatment. For example, FA increased in juveniles of Atlantic salmon after experimental maternal cortisol enhancement where the highest level of FA was observed in offspring that had been challenged with both high prenatal cortisol levels and hyperthermia [22]. Similarly, corticosterone or cortisol treatment, either through the mother or directly into the egg, has resulted in increased FA in hatchlings in chickens, Japanese quails and damselfish [23][24][25].…”
Section: Introductionmentioning
confidence: 99%